2006
DOI: 10.1088/0953-8984/19/1/016005
|View full text |Cite
|
Sign up to set email alerts
|

Possible reappearance of the charge density wave transition in MxTiSe2compounds intercalated with 3d metals

Abstract: Measurements of the electrical resistivity have been performed on MxTiSe2 compounds intercalated with 3d metals (M = Cr, Mn, Fe, Ni) up to x = 0.5. The charge density wave (CDW) transition which is observed in pure TiSe2 below ∼200 K disappears for intercalation x>0.1, while a further increase of the intercalant content (x≥0.25, M = Cr, Mn or Fe) leads to the appearance of pronounced anomalies in the temperature dependences of the resistivity in the same temperature range where the CDW transition takes place i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 45 publications
(80 reference statements)
1
30
0
Order By: Relevance
“…It was established that the substitution of titanium or selenium as well as the intercalation of a small amount of other atoms leads to the disappear ance of the transition into the CDW state. However, anomalies in the behavior of physical properties at high concentrations of intercalated atoms (x ≥ 0.25) were found for some M x TiSe 2 systems (M = Cr, Mn) in the temperature range from 120 to 250 K; they were explained by the transition return into the CDW state [7]. Therefore, it is possible that structural distortions in the TiSe 2 matrix itself, which is prone to the forma tion of the superstructure and the CDW formation, start in the Ni 0.5 TiSe 2 compound upon heating above 260 K; and then intercalated nickel atoms are disor dered with the further increase in temperature.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…It was established that the substitution of titanium or selenium as well as the intercalation of a small amount of other atoms leads to the disappear ance of the transition into the CDW state. However, anomalies in the behavior of physical properties at high concentrations of intercalated atoms (x ≥ 0.25) were found for some M x TiSe 2 systems (M = Cr, Mn) in the temperature range from 120 to 250 K; they were explained by the transition return into the CDW state [7]. Therefore, it is possible that structural distortions in the TiSe 2 matrix itself, which is prone to the forma tion of the superstructure and the CDW formation, start in the Ni 0.5 TiSe 2 compound upon heating above 260 K; and then intercalated nickel atoms are disor dered with the further increase in temperature.…”
Section: Resultssupporting
confidence: 59%
“…In addition, metal vacancies and atoms in partially occupied layers can undergo order ing within a single V v layer and between such layers. This circumstance leads to a variety of possible struc tural phase transformations, which are associated with transitions into the state with the commensurate (incommensurate) charge density wave as well as with order-disorder type transitions [7].…”
Section: Introductionmentioning
confidence: 97%
“…[12,13] This doping effect is similar to that in TM x TiSe 2 compounds. [14] TiSe 2 shows a structural phase transition induced by a CDW below ∼200 K. Similar to IrTe 2 , the structural transition is accompanied by distinct anomalies in transport, magnetic and thermodynamic properties. Intercalation of 3d transition metals in TM x TiSe 2 (TM =Cr, Mn, Fe, Ni) suppresses the structural transition which disappears at x ∼0.1.…”
Section: Introductionmentioning
confidence: 93%
“…Some considered it a realization of the excitonic CDW mechanism proposed by Kohn in the 1960's [11,12]; but different models were proposed to interpret the electronic structure, depending on whether system was argued to be a semimetal, or a semiconductor [13,14]. With Cu doping, it was found that the CDW transition temperature quickly drops, similar to other M x TiSe 2 's (M=Fe,Mn,Ta,V and Nb) [15,16,17,18]. Meanwhile, the superconducting phase emerges from x ∼ 0.04 and reaches the maximal transition temperature of 4.3K at x ∼ 0.08, then decreases to 2.8K at x ∼ 0.10.…”
mentioning
confidence: 92%